An Adaptive Skill Framework For Vietnamese Outbound Tour Leaders: Evaluation And Proposal - Huynh Nguyen, Tran (Digital Repository of Theses - SSBM Geneva, 2025)
This study addresses the critical need for an updated competency framework for Vietnamese outbound tour leaders, bridging the gap between existing vocational standards basing on VTOS (2013) and evolving market demands. Employing a mixed-methods approach, the research integrates in-depth 10 interviews with 10 industry experts and a quantitative survey with 20 active tour leaders. The primary research instrument, a scenario-based skills assessment, was developed to measure proficiency across 14 key skills, which were then compared with 400 archival customer feedback forms. The adjusted regression analysis demonstrates that these dimensions, particularly Core Professional Competence (β=0.555) and Operational Management and Planning (β=0.299), are the most influential predictors of a tour leader's overall proficiency. However, the analysis also reveals a disconnect between these skills and customer satisfaction, suggesting that while the skills collectively explain variance in feedback, no single factor's contribution is statistically significant. The study concludes by proposing an evidence-based skill framework for Vietnamese outbound tour leaders. This framework, grounded in empirical data, provides actionable insights for tour operators and training institutions to enhance recruitment, professional development, and performance evaluation. It highlights the importance of an integrated approach to skill development, moving beyond years of experience and simple feedback metrics to foster a more robust and adaptable workforce.